Brittney's Boutique: Tailoring a budget for function as well as fashion. (June 2017) - Stuebs, Martin; Bryant, Scott M.; Edison, Cari; Reese, Kate
Highlights: • This short, real-world managerial accounting case is flexible and versatile. • Students apply managerial accounting with Excel to analyze a business start-up. • Students prepare income statements, break-even analyses, and budgets. • Suggestions, solutions, spreadsheets, video and article resources are available. Abstract: This case is designed for use in an introductory managerial accounting course. The case provides you with the opportunity to extend and apply managerial accounting knowledge in the practical, real-world setting of managing the start-up of Brittney's Boutique, a student's entrepreneurial efforts in the retail fashion merchandising business. The case is intended to challenge you to: (1) use managerial accounting knowledge to prepare statements, analyses, and budgets; (2) recognize and understand the needs and challenges in starting a business; (3) apply Excel knowledge, skills and abilities; and (4) analyze and combine managerial accounting information to make judgments, conclusions and recommendations.